Taxonomia de porifera dos ecossistemas recifais de Maceió, Alagoas - Cedro, Victor Ribeiro (2013)
The sponges occurring on Alagoas shallow reefs (Brazilian NE) are poorly-known, with several species listed, but not formally described. From 51 species listed for the state, only 22 were formally described. This work increases the number of marine sponges recorded for Alagoas to 74, with four new species: Mycale alagoana Cedro et al., 2011, M. rubra sp nov., Rhabderemia meirimensis sp nov. and Plakina coerulea sp nov. Six demosponges poorly characterized and/or not recorded for the state were described: Acarnus innominatus Gray, 1867 (first record on the brazilian coastline), Biemna caribea Pulitzer-Finali, 1986 (first record on western tropical south atlantic), Lissodendoryx isodictyalis (Carter, 1862) and M. diversisigmata (Van Soest, 1984) (first record on western tropical south Atlantic), Stelletta beae Hajdu & Carvalho, 2003 (first record on Brazil’s NE), Plakortis angulospiculatus (Carter, 1882) and Cyamon aff. vickersii (Bowebank, 1864). Other demosponges recorded were: Aaptos aff. aaptos Schmidt, 1870, Clathria schoenus (De Laubenfels, 1936), Cliona vermifera Hanckock, 1867, Diplastrella megastellata Hechtel, 1965, Eurypon sp., Gastrophanella aff. implexa Schmidt, 1869, Geodia glariosa (Sollas, 1886), G. gibberosa Lamarck, 1815, Halichondria melanadocia De Laubenfels, 1936, Holoxea sp., Ircinia felix (Duchassaing & Michelotti, 1864), Mycale citrina Hajdu & Rutzler, 1998, M. magnirhaphidifera Van Soest, 1984, Stelletta anasteria Esteves & Muricy, 2005, Terpios fugax Duchassaing & Michelotti, 1864 and Xestospongia sp. The results appoints the occurrence of a high diversity of poriferans along Maceió’s shallow reefs, with 26 new records on the present study, mainly western tropical in composition, with a clear Caribbean affinity. The cluster analysis showed a clear-cut separation between the reefs next to and north of Maceió urban center. The diversity of marine sponges on Alagoas remains quite underestimated in absence of studies concerning deep-water reefs and sponges dredged from the continental shelf, together with the virtual absence of ecological data concerning the distribution of porifera along Alagoas coastal reefs.